Distribution of weed species and soil nitrogen, phosphorus, and potassium across various land uses in coastal areas - Muktamar, Z.; Setyowati, N.; Utami, K.; Haris, H. A.; Nurjanah, U.; Sukisno, S.; Hindarto, K. S. (International Journal of Agricultural Technology, 2025)
The survey identified a total of 81 weed species, which included 42 species of broadleaf weeds, 25 grasses, 9 sedges, and 5 ferns. The oil palm plantation exhibited the most weed diversity, with a total of 40 species, including 19 broadleaf, 13 grasses, 3 sedges, and 5 ferns. In contrast, the rice farm had the lowest weed diversity, consisting of just 8 species, including 3 broadleaves, 3 grasses, and 2 sedges. The number of weed species in oil palm plantations was comparable to that in rubber plantations, although greater than in coconut plantations. In coconut and oil palm plantations, broadleaf weed species were the most common, accounting for 58.05% and 50.89% of the total weed population, respectively. On the other hand, in rubber plantations and swamp land, grasses were the dominating weed species, making up 44.68% and 56.24% of the Summed Dominance Ratio (SDR), respectively. Melastoma affine D. Don was the dominant weed species in oil palm and rubber plantations, with an SDR of 9.44% and 7.09%, respectively, while Borreria alata Aubl. is the primary weed species in coconut plantations, with an SDR of 12.70%. However, in swamp land, Isachne globosa (Thunb.) O.K., a type of grass, makes up 14.43% of SDR. Furthermore, the swamp land exhibited the highest soil nitrogen concentration (5982.53 mg/kg). The coconut plantation had the highest soil phosphorus level (2.76 mg/kg), while the rice farm had the highest soil potassium (226.18 mg/kg). The Pearson correlation analysis revealed a negative association between the prevalence of broadleaf weed species and grasses. Likewise, there was a negative correlation between broadleaf weeds and soil N, suggesting that these specific weeds can compete under low nitrogen. The discovery of this study has advantageous implications for the management of weed control in coastal environments.